DESKRIPSI MISKONSEPSI PESERTA DIDIK PADA MATERI PEMANASAN GLOBAL DI SMA NEGERI 1 SERAWAI - Bayu Krisna; Edy Tandililing; Syaiful B Arsyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
ABSTRAKThis study aims to determine the state of misconceptions on global warmingexperienced by students at SMA Negeri 1 Serawai and see whether there aredifferences in the proportion of misconceptions between male and femalestudents. The research method used is descriptive in the form of quantitativeresearch. The subjects of this study were students of class XI science for the2018/2019 academic year and the data was student answer sheets for thediagnostic test (AREPDiT). The results showed that 22 out of 29 people (75.86%)students had misconceptions about global warming. When viewed by gender, thenumber of male students who experienced misconceptions was 14 out of a total of16 people (87.50%), while the number of female students who experiencedmisconceptions was 8 out of a total of 13 people (53.84%). Thus, it can be saidthat male students experience greater misconceptions than female students.Keywords: Description, Global Warming, Misconception, Students